Effects of Tillage Methods on Carbon and Nitrogen Sequestration and Soil Microbial Stoichiometric Equilibrium in a Black Soil Farmland with Full Return of Straw to the Field - Meiren Rong; Zhigang Wang; Xiangqian Zhang; Zhanyuan Lu; Lanfang Bai; Zhipeng Cheng; Tianhao Wang; Yajing Zhang; Hongwei Liang; Tiantian Meng; Lingyue Liu; Fang Luo (Agronomy, 2025)
Long-term irrational farming practices and low return of organic materials to the fields in the black soil area have led to reduced soil carbon and nitrogen stability and nutrient imbalance, which in turn affect soil fertility and crop yields. Straw return is an effective way to enhance soil organic matter and crop productivity, but the effects of long-term straw return under tilling practices on carbon and nitrogen sequestration and soil microbial stoichiometric equilibrium in black soil need to be further investigated. This study investigated the physical, chemical and biological properties of the 0–60 cm soil layer under deep tillage with straw return to the field (DTS), deep harrow with straw return to the field (DHS), rotary tillage with straw return to the field (RTS), no tillage with straw return to the field (NTS), and conventional tillage with straw removal (CT) on the basis of seven consecutive years of tillage pattern location trials in the black soil area of eastern Inner Mongolia. The results showed that DTS and NTS significantly increased the soil organic carbon (SOC), soil total nitrogen (TN), soil microbial biomass carbon (MBC), soil microbial biomass nitrogen (MBN) contents, and the SOC/TN ratio in the 0–40 cm soil layer, enhancing soil carbon and nitrogen sequestration capacity, while the concomitant increase in the average MBC/MBN ratio in the plow layer from 6.8 to 8.2. The soil microbial quotient increased by 29.0% and 26.2%, respectively, and the stoichiometric imbalance ratio decreased by 7.9% and 5.7%, respectively. Meanwhile, in terms of maize yield from 2018 to 2024, DTS showed the most stable and significant yield increase with 41.53%. Whereas NTS showed a higher yield increase potential with a 27.36% increase in yield as the number of years of straw return increased. Therefore, DTS and NTS are superior tillage methods to improve the quality of the black soil tillage layer, to promote soil microbial carbon and nitrogen balance, and to increase crop yields.